Potencial genético de genitores de cana-de-açúcar com base em cruzamentos biparentais - Santana, Priscilla Neves de (2013)
An adequate choice of genitors to be crossed to generate genetic variability is essential to increase the efficiency of sugarcane breeding program. The combining ability of genotypes in crosses constitutes a good measure of genetic potential in future crosses. The aim of this study was to evaluate the genetic potential of sugarcane genotypes based on biparental crosses of sugarcane breeding programs from the Interuniversity Network for the Development of Sugarcane Trade (PMGCA / RIDESA). The basic variable used was the rate of selection of each cross population (full sib family) in the initial phase of the program (T1), resulting from the selection practiced evaluating variables of primary importance for the species. The average selection rate of each family was predicted using BLUP methodology. Data analysis was performed using Method IV proposed by Griffing (1956), adapted to the set of crosses available, detailing the effects of General Combining Ability (GCA) and Specific Combining Ability (SCA). The predicted effects of SCA were correlated with genetic similarity estimates obtained using the Dice coefficient from SSR markers and the Malécot coancestry coefficient. It was detected significant effects of GCA, showing the possibility of selection of parents based on this parameter. Although not statistically tested, SCA showed determination coefficient higher than CGC. The genetic similarity obtained by coancestry coefficient showed a significant correlation with SCA, although of low magnitude. There was no significance for the correlation between genetic distance based on SSR marker and SCA. It was concluded that the rate of selection is efficient to select potentially promising parents in the first stage of selection in sugarcane.